Pengetahuan dan Sikap Ibu Postpartum terhadap Program Keluarga Berencana di RSUD Dr. Sam Ratulangi Tondano - Lukas, Andrie E.; Mongan, Suzanna P.; Wagey, Freddy W. (Universitas Sam Ratulangi, 2020)
Abstract: Family planning program is a program of the government of the Republic of Indonesia that aims to achieve a healthy and prosperous family by limiting births. Tondano is the center of Minahasa district and has four sub-districts and population of 70,467 people with a female number of 34,800. Data on women using family planning showed a number of 25,749 people which indicates a large and growing population. This study was aimed to evaluate the level of knowledge and attitudes of mothers towards the family planning program. This was a descriptive study with a cross-sectional design. Data were obtained by using questionnaire as the instrument. Respondents were 50 postpartum mothers who came to Dr. Sam Ratulangi Hospital Tondano and were willing to fill in the distributed questionnaires. The results showed that 92% of responsdents had good knowledge and 8% had poor knowledge. Meanwhile, based on the attitudes of respondents, 70% of them were positive and 30% were negative. In conclusion, family planning services based on the level of knowledge and attitudes of postpartum mothers at Dr. Sam Ratulangi Hospital Tondano were good or above average. Albeit, postpartum mothers who had good knowledge may not necessarily had good attitudes.Keywords: family planning, contraception, knowledge, attitudeÂ Abstrak: Program Keluarga Berencana (KB) bertujuan untuk membentuk gerakan keluarga sehat dan sejahtera dengan cara membatasi kelahiran. Tondano merupakan pusat dari Kabupaten Minahasa dan memiliki empat kecamatan dengan populasi sebesar 70.467 jiwa dan jumlah perempuan sebesar 34.800 jiwa. Data perempuan yang memakai KB ialah 25.749 jiwa. Data tersebut menunjukkan jumlah penduduk yang banyak dan terus bertambah. Penelitian ini bertujuan untuk mengevaluasi tingkat pengetahuan dan sikap ibu postpartum terhadap program KB di RSUD Dr. Sam Ratulangi Tondano. Jenis penelitian ialah deskriptif dengan desain potong lintang. Pengambilan data menggunakan kuesioner sebagai instrumen penelitian. Responden penelitian ialah ibu postpartum yang datang di RSUD Dr. Sam Ratulangi Tondano dan bersedia mengisi kuesioner yang dibagikan. Hasil penelitian mendapatkan total 50 responden. Sebanyak 92% ibu memiliki pengetahuan baik dan 8% memiliki pengetahuan kurang baik. Untuk pengukuran sikap dari responden, sebanyak 70% wanita bersikap positif dan 30% yang bersikap negatif. Simpulan penelitian ini ialah bahwa pelayanan KB berdasarkan tingkat pengetahuan dan sikap ibu di RSUD Dr. Sam Ratulangi Tondano sudah baik atau di atas rata-rata. Walaupun demikian ibu yang memiliki pengetahuan baik belum tentu memiliki sikap yang baik.Kata kunci: keluarga berencana, kontrasepsi, pengetahuan, sikap